Attribute-based encryption supporting arbitrary conjunctive key word search - Yan SONG; Zhen HAN; Dong CHEN; Jin-hua ZHAO (Tongxin xuebao)
A new searchable encryption scheme was proposed in prime order bilinear groups based on the attribute-based encryption and polynomial equation.The scheme,in which each conjunctive-keyword ciphertext can be searched by a number of users,may significantly reduce the overhead of network and sending nodes' computation in the application of fine-grained access control.Meanwhile,the scheme facilitates the flexibility of conjunctive search by supporting arbitrary conjunctive search of the keywords.At last,the performance was analyzed and compared with some recent conjunctive search schemes.